Heuristic Solutions for the 2D Bin-Packing Problem with Varied Size - Fernandes, Eduardo Augusto Militão; Noronha, Thiago Ferreira de; Coco, Amadeu Almeida (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2024: Anais da XXXIV Brazilian Conference on Intelligent Systems, 2024)
This work addresses the 2D Bin-Packing Problem with Varied Size and proposes heuristic solutions for it. An extensive literature review on the problem is carried out, and the state-of-the-art literature algorithm for its variation with guillotine constraint is reproduced in order to validate the reported results. It is also used to build a baseline which is compared with a proposed improvement for this algorithm in order to enable the addition of a new constraint to the problem that meets an industry demand for its practical application.